بلفتني’منيرة. - بلفتني منيرة; غدايفي هند (University of Eloued جامعة الوادي, 2024)
Abstract: This study aimed to reveal the symptoms of post-traumatic stress disorder among diabetic amputees according to the variables of sex and age, as well as to reveal the prevalence of symptoms of this disorder among patients who have experienced the trauma of amputation and the psychological effects that followed. The researchers relied on the descriptive analytical approach where was the sample chosen intentionally way, by dealing with all diabetic amputees who frequent Al Hakim Okbi in Guelma City during the time period between March and June of the year 2022, which consisted of (25) patients who completed a full month after the amputation, with the application of the American Psychiatric Association’s Post Traumatic Stress Disorder Scale PCL-5 translated and refereed Fifth Edition. The study found the emergence of post*traumatic stress disorder symptoms with varying degrees of severity, with presence of statistically significant differences due to the variables of gender and the absence of statistically significant differences due to age in the study sample. ملخص: هدفت هذه الدراسة الى الكشف عن أعراض اضطراب ما بعد الصدمة لدى مرضى السكري مبتوري الأطراف حسب متغيري الجنس والسن، وكذا الكشف عن معدل انتشار أعراض هذا الاضطراب بين المرضى الذين عايشوا صدمة البتر وما لحقها من آثار نفسية، اعتمدت الباحثتان على المنهج الوصفي التحليلي، أن تم اختيار العينة بطريقة قصدية وذلك بالتعامل مع جميع مرضى السكري مبتوري الأطراف المترددين على مستشفى الحكيم عقبي بمدينة قالمة خلال الفترة الزمنية الممتدة مل بين شهري مارس وجوان من العام 2022 والتي بلغ قوامها (25) مريضا ومريضة، على أن يكون المرضى قد استوفوا مدة شهرا كاملا بعد عملية البتر مع تطبيق مقياس اضطراب ما بعد الصدمة PCL-5 من اصدار الجمعية الأمريكية للطب العقلي النسخة الخامسة المترجمة والمحكمة، وتوصلت نتائج الدراسة الى بروز أعراض اضطراب ما بعد الصدمة بدرجات متفاوتة في الشدة مع وجود فروق ذات دلالة إحصائية تعزى لمتغير الجنس وعدم وجود فروق ذات دلالة إحصائية تعزى لمتغير السن لدى عينة الدراسة.
دراسة ميدانية بمستشفى الحكيم عقبي مدينة قالمة
Keywords: اضطراب ما بعد الصدمة; مبتوري الأطراف; داء السكري; Post-Traumatic Stress Disorder; Amputees; Diabetic